PENGARUH PENGALAMAN KERJA, INDEPENDENSI, OBYEKTIFITAS, INTEGRITAS DAN KOMPETENSI TERHADAP KUALITAS HASIL AUDIT (Studi Kasus Pada Auditor Inspektorat Kota/Kabupaten di Jawa Tengah) - Harvita Yulian Ayuningtyas; Sugeng Pamudji (Diponegoro Journal of Accounting, 2012)
This study aims to examine the impact of experience, independency, objectivity, integrity, and competence to the quality of audit result of local government using multiple regression analysis . The object of this study is the city or district inspectorate in central java as goverment internal auditor. This study is an empirical study with purposive sampling techniques of data collection. Respondents in this study are the Inspectorate of Semarang, Pekalongan, Salatiga district, Semarang and Kendal. There are six variables in this research that consist of five independent variables namely experience, independency, objectivity, integrity, and competence and one dependent variable that is the quality of audit result. According to the results of research, it can be concluded that objectivity, integrity and competence significantly affect the quality of audit result, while experience and independence did not significantly affect the quality of audit result. The coefficient of determination indicates that the objectivity, integrity and competence simultaneously affect the dependent variable (the quality of audit result) of 60.10%, while the remaining 39.90% influenced by other factors.